Treatment patterns and use of healthcare resources of patients with atherosclerotic cardiovascular disease and hypercholesterolemia and patients with familial hypercholesterolemia in Spain: Protocol of the Reality study - Barrios, Vivencio; Castellanos, Mar; Campuzano Ruiz, Raquel; Gómez Cerezo, Jorge Francisco; Egocheaga Cabello, Isabel; Gámez, José M.; Martínez López, Icíar; Mostaza, José María; Morant Talamante, Nuria; Parrondo, Javier; Sicras Navarro, Aram; Pérez Román, Inés; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Atherosclerotic cardiovascular diseases (ASCVD) and dyslipidemia are associated to a higher risk of cardiovascular events, mortality, use of healthcare resources and costs. In Spain, the evidence about the administration of lipid-lowering treatments in clinical practice, and their clinical effectiveness in patients with ASCVD and hypercholesterolemia and patients with FH is scarce. Therefore, a multidisciplinary working group of cardiologists, family physicians, internal medicine specialists and neurologists was gathered for the Reality study. The aim of this study is to describe the demographic and clinical characteristics, comorbidities, and concomitant medication of patients with ASCVD and hypercholesterolemia and of patients with familial hypercholesterolemia (FH). The use of healthcare resources and costs associated to the management of these diseases after their diagnosis were also considered. Methods This is an observational and retrospective study, based on the BIG-PAC® database, which includes the electronic medical registries (EMRs) of 1.8 million people from 7 Autonomous Communities in Spain (including public primary care centers and hospitals). The study includes patients who had a new or recurrent episode of ASCVD during the recruitment period (from 01/01/2017 to 31/12/2018). The index date will be defined as the date of the ASCVD event, and the follow-up period will be 24 months. According to their first diagnosis in the database, patients will be classified as ASCVD (5 groups: stable/unstable angina, acute myocardial infarction, ischemic stroke, transient ischemic attack, and peripheral arterial disease) or FH. Discussion This study aims to analyze the treatment patterns and use of healthcare resources of ASCVD and FH in Spain. The prevalence of these disorders will also be estimated. Due to the high morbidity and mortality associated with these diseases, it is expected that our study will provide useful information for healthcare systems and decision makers to improve the management of these disabling diseases.